Successful Multidrug-Resistant Tuberculosis Treatment Without HIV Viral Suppression: A Missed Opportunity - Geiger, Keri; Patil, Amita; Budhathoki, Chakra; Dooley, Kelly E; Lowensen, Kelly; Ndjeka, Norbert; Ngozo, Jacqueline; Farley, Jason E (Journal of acquired immune deficiency syndromes (1999), 2023)
Coinfection with multidrug-resistant tuberculosis (MDR-TB) and HIV is common, but few published studies examine how undergoing MDR-TB treatment affects HIV disease indicators. Using data from a nested, retrospective cohort of people with HIV (PWH) and successful MDR-TB treatment outcomes, we built multivariable regression models to explore correlates of HIV viral suppression at MDR-TB treatment completion. Among 531 PWH successfully treated for MDR-TB, mean age was 37.4 years (SD 10.2, interquartile range 30-43), 270 (50.8%) were male, 395 (74.4%) were virally suppressed at MDR-TB outcome, and 259 (48.8%) took bedaquiline. Older age (adjusted odds ratio [aOR] 1.04, 95% confidence interval [CI]: 1.01 to 1.06) increased odds of viral suppression, while having a prior TB episode (aOR 0.45, 95% CI: 0.31 to 0.64), having a detectable viral load at MDR-TB treatment initiation (aOR 0.17, 95% CI: 0.09 to 0.30), living in a township (aOR 0.49, 95% CI: 0.28 to 0.87), and being changed from efavirenz-based antiretroviral therapy (ART) to a protease inhibitor due to bedaquiline usage (aOR 0.19, 95% CI: 0.04 to 0.82) or not having an ART change while on bedaquiline (aOR 0.29, 95% CI: 0.11 to 0.75) lowered odds of viral suppression. Changing from efavirenz to nevirapine due to bedaquiline usage did not significantly affect odds of viral suppression (aOR 0.41, 95% CI: 0.16 to 1.04). Increased pill burden and adverse treatment effects did not significantly affect HIV viral suppression while switching ART to a protease inhibitor to accommodate bedaquiline or not changing ART while taking bedaquiline did, suggesting that PWH and MDR-TB may benefit from additional support if they must switch ART.